The Effect of Corporate Governance on Company Financial Performance with Human Capital Investment as a Mediating Variable - Afifah Wanda Inas Asputri; Hersugondo Hersugondo (Jurnal Bisnis dan Manajemen, 2023)
This study aims to explore the influence of corporate governance on a company's financial performance, with human capital investment serving as a mediating factor. Within this investigation, the company's financial performance is regarded as the dependent variable, while Good Corporate Governance (GCG) is treated as the independent variable. Furthermore, human capital investment is introduced as a mediating variable. A dataset comprising 258 data points was collected from a sample of 43 financial sector companies listed on the Indonesia Stock Exchange between 2015 and 2020. Secondary data was utilized for this study, and the purposive sampling method was employed. The Partial Least Squares-Structural Equation Modeling (PLS-SEM) technique, implemented through the SmartPLS 4.0 program, was utilized to test the research hypotheses. The findings of this study reveal a significant and positive relationship between GCG and company financial performance, both of which exert a notable influence on human capital investment. Moreover, the results suggest that human capital investment acts as a mediator in the relationship between Good Corporate Governance (GCG) and company financial performance. Additionally, it is evident that GCG significantly and positively impacts the company's financial performance